Establishing the functional properties of chloroplast membrane material for food applications - Sucharit, Poramat (2022)
Chloroplasts are abundant photosynthetic organelles tightly packed with a complex membrane system containing lipophilic nutrients such as carotenoids and tocopherol. Through physical extraction methods, the chloroplastidial membrane material (CMM) can be prepared with different degrees of membrane integrity. While some centrifuged pellet samples show a more condensed membrane material, additional osmotic pressure and high-pressure treatment could lead to a more dispersed and a completely disintegrated membrane system, respectively. All the CMMs prepared are rich in bioactive molecules with the pellet CMMs enriched in lipophilic nutrients (i.e., Chl a, Chl b, lutein, β-carotene, α-tocopherol and various fatty acids) and micronutrients such as iron; supernatant samples are enriched in minerals (e.g., P and Mg). The use of a juicer to isolate chloroplasts from the confinement of undigestible cell walls proved to be a simple and efficient method to prepare a chloroplast-rich extract.